Implementasi media pembelajaran mosyajiroh pada mata pelajaran fikih kelas 5 di MIN 2 Kota Malang - Ramadhani, Akhmad (Maliki Interdisciplinary Journal, 2024)
This research aims to determine the implementation of Mosyajiroh learning media in class 5 fiqh subjects at MIN 2 Malang City. This research uses a qualitative method with a descriptive approach. Data was collected through observation, interviews and documentation. The results of the research show that the implementation of Mosyajiroh learning media in class 5 fiqh subjects at MIN 2 Malang City has been carried out well. This is proven by: (1) careful planning, (2) implementation according to plan, (3) continuous evaluation, and (4) increased student learning outcomes. Mosyajiroh learning media has proven to be effective in increasing student interest, motivation and learning outcomes in fiqh subjects.